Tecnologia social e desenvolvimento sustentável: o contexto de artesãos organizados em associações na região do Cariri - Macêdo, Jôsanny Lopes de (2014)
The model of development, characterized by the concentration of wealth and centered on the economic outlook, resulted in social inequality and worsening environmental problems (Sachs, 2008). By the late nineteenth century, some scholars began to devote to developing the concept and applicability of social technology, which refers to a set of methods, techniques or products considered replicable and built through knowledge of the population itself, with potential to promote sustainable development (RTS, 2013). As an example of activity that can be developed on the foundations of social technology and sustainability, one can mention the craft (PEN, 2010). Thus, this research has the overall objective to analyze the effects of social technology used by artisans organized in associations, to sustainable development. This is a qualitative study, the interpretive type. The research strategy comprises the single case study, and with the unit of analysis Mocotó Community Association of Várzea Alegre city, located in Cariri Region. Data collection was conducted through focus group techniques, semi-structured interviews and non-participant observation. Participated in the data collection process eight artisans of the Mocotó Community Association. To realize the data analysis applied to content analysis. According to the main results, it was found that small-scale production of the Mocotó Community Association appears as favorable to sustainable social development technology, since it produces significant effects, from the perspective of economic, social, environmental and cultural sustainability. The associative work generates employment and income, whose members have the potential to defray the expenses of the group and generate profit. Minimizes the differences between the conditions of life emphasizing basic rights of the population. Encourages the use of natural elements without compromising the integrity of the environment. Regards both popular knowledge as scientific knowledge, valuing cultural diversity.